2020
DOI: 10.4067/s0717-95022020000601566
|View full text |Cite
|
Sign up to set email alerts
|

Human Skull Base Asymmetry Analysis

Abstract: Since the asymmetry is generally accepted entity which can be detected on human skulls, the goal of this study was to evaluate the presence and degree of skull base asymmetry and analyze it in relation to sex. The study included 60 skulls. Gender identification was estimated according to the external occipital protuberance, mastoid process, supraorbital margin and glabella. The asymmetry was assessed by analyzing the distance from the bilateral foramina (foramen ovale, foramen spinosum, carotid canal, foramen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Moreover, we can point to high variability in the skull-base foramina size, with the biggest differences between diameters of the left and the right carotid canal and foramen ovale. [12]. In the Greek population examined by Chovalopaulou et al, the highest FA was found in the skull-base region [9].…”
Section: Skull Symmetrymentioning
confidence: 91%
“…Moreover, we can point to high variability in the skull-base foramina size, with the biggest differences between diameters of the left and the right carotid canal and foramen ovale. [12]. In the Greek population examined by Chovalopaulou et al, the highest FA was found in the skull-base region [9].…”
Section: Skull Symmetrymentioning
confidence: 91%
“…Additionally, carotid canals naturally exhibit a high level of natural asymmetry. 53 Classification CICAH lacks a standard classification system, as many of the reviewed reports noted. Even the terms 'aplasia' and 'hypoplasia' are used interchangeably.…”
Section: Diagnostic Issuesmentioning
confidence: 99%
“…Anthropological landmarks, which are marked in Figure 1, were the subject of numerous studies conducted at the Institute of Anatomy, Faculty of Medicine in Novi Sad (Knezi et al, 2020;Pupovac et al, 2020;Radosevic et al, 2020). This study was carried out in order to highlight the significance of the basic morphological researches, as well as to contribute to the preservation of their knowledge.…”
Section: Introductionmentioning
confidence: 99%